Finansal Krizlerin Belirleyicileri: Gelişmiş ve Gelişmekte Olan Ülkelerin Karşılaştırmalı Analizi - Aytül Ganioğlu (Turkish Economic Association, 2012)
– In this study, the main purpose is to analyze the factors that stimulate the probability of financial crises. The period of analysis covers the years of 1970-2008, thereby including the impact of recent global financial crisis. The analysis aims to make a comparison for the developed and developing country financial crises separately. Panel logit estimation technique is used for the analysis which includes 24 developed and 26 developing countries, amounting to 50 countries as total. According to estimation results, current account deficit carries the risk of raising the probability of financial crises significantly both in advanced countries and developing countries. Furthermore, credit booms during the last five-year period, as well as monetary expansion, contributed to the probability of financial crises especially in developed countries.
Keywords: G01; C33; G18; G21; G28; 330